Genetic characterization of genotype VII.1.1 Newcastle Disease viruses from commercial and backyard broiler chickens in Egypt - Abdelmonem Dewidar; Azza El-Sawah; Salama Shany; Al-Hussien Dahshan; Ahmed Ali (German Journal of Veterinary Research)
The small-scale and backyard-raised poultry are extensively growing in Egypt. However, low biosecurity and/or vaccination practices are adopted. The current study was conducted to investigate and molecularly characterize Newcastle Disease (ND) strains circulating in small-scale and backyard poultry sectors in Giza governorate in Egypt from July 2018 to April 2020. Twelve broiler flocks (6 commercial and 6 backyard flocks) suffering from respiratory and/or nervous signs were included. Virus isolation and molecular characterization were conducted. In the present study, three NDV isolates were isolated from commercial (n=2) and backyards (n=1) flocks. The isolated viruses maintained the multi-basic motif112RRQKRF117 in the fusion protein cleavage site indicative of their virulent nature. Phylogenetically, the viruses are closely related to genotype VII.1.1. ND viruses are genetically different from NDV genotype II vaccine strains. Deduced amino acid sequences of the fusion (F) protein showed an amino acid change of S278P in the heptad repeat (HRb) in the two NDV isolates from commercial farms. Other amino acid substitutions were observed including the change at positions 442 (A/T) in the two commercial flocks isolates and position 317 (A/S) in the backyard ND isolate. Few silent nucleotide mutations were also observed in the F protein of the NDV isolate from the backyard flocks. In conclusion, the current study reports the genetic identification of virulent NDV viruses from commercial or backyard flocks related to genotype VII.1.1. ND circulating in Egypt. The amino acid substitutions and nucleotide changes warrant the need for continuous surveillance of NDV in these growing poultry sectors considering their importance as a spot for extensive NDV circulation and as the main source for live bird markets in Egypt.